2021
DOI: 10.1155/2021/6649574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytochemical, Antioxidant, and Memory-Enhancing Activity of Garuga pinnata Roxb. Bark and Bryophyllum pinnatum (Lam) Oken. Leaves

Abstract: Garugapinnata Roxb. (Burseraceae) is a medium-sized tree widely available all over the tropical regions of Asia. Bryophyllum pinnatum (Lam) Oken. (Crassulaceae) is an indigenous and exotic plant grown in tropical regions. Both plants have been used for their anti-inflammatory, antioxidant, anticancer, wound healing, antidiabetic activities, etc. This investigation was designed to explore the result shown by methanolic extract of Garuga pinnata bark and Bryophyllum pinnatum leaves, on cognitive power and retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The antioxidant activity of plant extract was checked by using DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging activity, according to previous methods with slight modification [ 29 31 ]. At first, the stock solution of 0.1 mM of DPPH, 1 mg/ml of ascorbic acid, and test solutions were prepared in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The antioxidant activity of plant extract was checked by using DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging activity, according to previous methods with slight modification [ 29 31 ]. At first, the stock solution of 0.1 mM of DPPH, 1 mg/ml of ascorbic acid, and test solutions were prepared in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison with other extracts (AE and PEE) obtained from the leaves, the EE showed the greatest radical inhibitory effect by DPPH, reaching a maximum inhibitory effect of 49.5 ± 5.6% (2000 µg/mL) [ 106 , 156 ]. The antioxidant property of ME from leaves showed 69.77% of free radical inhibition (100 µg/mL) of DPPH [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anticonvulsant activity from the ME of roots and stems of K. pinnata decreased with increased doses of the ME of roots, whereas the effect of the ME of stems was dose-dependent (it increased with higher doses) and this effect was preserved when the mixture of chloroform and ethyl acetate were tested. The dose of 400 mg/kg of the ME significantly improved the memory and learning of mice [ 62 , 80 ]. A study utilizing a larval zebrafish model was conducted to assess the potential of the AE obtained from K. pinnata leaves; the results indicated that the AE exhibited both anxiolytic and psychoactive effects, in a dose-dependent manner [ 173 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sped-up injury mending saw with the methanol concentrate could be credited to the synergistic activity of its phytoconstituents, especially flavonoids and tannins, known for their mitigating and cell reinforcement properties. Flavonoids have been accounted for Journal of Survey in Fisheries Sciences 10(3) 900-902 2023 902 to advance injury mending by upgrading collagen combination, angiogenesis, and fibroblast expansion, while tannins show astringent and antimicrobial impacts, supporting injury conclusion and forestalling contamination (Bhandari et al, 2021). The predominant injury mending viability of the methanol concentrate may likewise be credited to its capacity to extricate many bioactive mixtures from Bryophyllum pinnatum leaves, including both polar and non-polar constituents.…”
Section: Discussionmentioning
confidence: 99%